Staged Osteotome Sinus Floor Elevation for Progressive Site Development and Immediate Implant Placement in Severely Resorbed Alveolar Bone: A Case Report - Saad Al-Almaie (Case Reports in Dentistry)
This case report discusses osteotome sinus floor elevation (OSFE) and immediate placement in 2 stages in severely resorbed alveolar bone height in which multiple implant placement is not otherwise feasible due to a lack of initial stability. The first implant placed using OSFE without bone grafting prepares the adjacent resorbed sites for further implant placement in the sinus areas, which allows for better initial stability and early functional loading. This process avoids the conventional extensive lateral approach for sinus lifting and bone grafting procedures even in extremely resorbed alveolar bone.